How to search and manage references with a specific referencing style using google scholar: From Step-by-step Processing for Users to the Practical Examples in the Referencing Education - Azizah, Nissa Nur; Maryanti, Rina; Nandiyanto, Asep Bayu Dani (Indonesian Journal of Multidiciplinary Research, 2021)
The objective of this study was to demonstrate an easy way along with a step-by-step process in searching references as well as to show the technique of writing referencing style to make the manuscript fit for publication in journals. The study method was carried out in many steps with using the Google Scholar search engine, included search for articles in a journal, obtaining citations from author, and constructing a reference style. As a practical example, we will look for articles about engineering education with used IJoST, JESTEC, JEET, and IJCSNE journals, and there are several style references such as, APA, MLA, Vancouver, Harvard, Chicago/Turabian, and IEEE style. We identified that Google Scholar may be utilized as a teaching resource and beginner authors who are learning how to create articles.